A molecular phylogeny of Speonemadus Jeannel, 1922 with description of two new species from Morocco (Coleoptera: Leiodidae: Cholevinae: Anemadini) - Fresneda, Javier; Faille, Arnaud; Fery, Hans; Ribera, Ignacio (Zootaxa, 2019)
The genus Speonemadus Jeannel, 1922 currently includes 12 species distributed in the Western Mediterranean (Iberian Peninsula, North Africa, Sicily and continental Italy). Two new species are described from Morocco, S. brusteli sp. n. from the Rif and S. comasi sp. n. from the High Atlas, the first in the S. vandalitiae-group of species and the second with an isolated position within the genus. Two species are also resurrected from synonymy, S. pulchellus (Reitter, 1885) stat. rest. (former synonym of S. orchesioides (Fairmaire, 1879)) and S. gracilis (Kraatz, 1870) stat. rest. (former synonym of S. vandalitiae (Heyden, 1870)), raising the total number of species of the genus to 16. Lectotypes are designated for Anemadus pulchellus Reitter, 1885, and Anemadus tenuipes Peyerimhoff, 1917. A molecular phylogeny of the genus Speonemadus is presented, based on a combination of mitochondrial and nuclear genes and including seven of the currently recognised species, one of the newly described (S. brusteli sp. n.) and the two reinstated taxa. The genus is estimated to have diversified from the late Miocene (Tortonian), with successive cladogenetic events related to the isolation of landmasses between Iberia and North Africa, including the opening of the Strait of Gibraltar at the end of the Messinian. The distribution of some of the species of Speonemadus remains still uncertain, due to their frequent misidentification and the problems with their taxonomic status.